0089 Recovery from mental condition: is it different between TBI/non-TBI. (23rd June 2014) - Lin, Kuan-Han; Shu-Chu Shiao, Judith; Liao, Shih-Cheng; Kuo, Chun-Ya; Leon Guo, Yue; Guo, Nai-Wen
Abstract : Objectives: This study aimed to determine the rates of psychological symptoms among those with traumatic brain injury (TBI) and with non-TBI at 3 months and 12 months after occupational injury and to examine the change in psychological status over time. Method: Our study candidates were injured workers in Taiwan who were hospitalised for 3 days or longer and received hospitalisation benefits from the Labour Insurance. A self-reported questionnaire including Brief Symptom Rating Scale (BSRS-50) and Post-traumatic Symptom Checklist (PTSC) was sent to workers at 3 months and 12 months. Results: Among 853 injured workers who completed the questionnaire at 3 and 12 months, regarding to the severity of BSRS score, 7.8% of those with TBI had recovered at 12 months, comparing with 8.1% in those with non-TBI. On the other hand, approximately11.6% of those with TBI had recovered from post-traumatic stress symptoms at 12 months, comparing with 9.7% among those with non-TBI. Injured workers with TBI had lower rate of recovery from psychological symptoms, comparing with non-TBI. Conclusions: A significant proportion of victims with TBI and non-TBI suffered psychological symptoms after injury. The identification and treatment of psychological symptoms are important for optimal adaptation after traumatic injury.